Corneal donations in South Africa: a 15-year review - York, Nicholas (Division of Ophthalmology, 2018)
Background: Corneal pathology is one of the leading causes of preventible blindness in South Africa. A corneal transplant procedure can restore, or significantly improve vision in most of these patients. In current South African clinical practice however, there is a gross shortage of corneal tissue available to ophthalmologists to perform these procedures. There is little published data on corneal donations in South Africa describing the magnitude of the current problem. Objectives: To describe trends in the number of corneal donors per year, the number of corneal transplants performed each year, the origin of corneal donors, the allocation of corneas to the public or private sector and the demographics of corneal donors in South Africa. Methods: A retrospective review of all corneal donations made to South African eye banks during a 15-year study period from 1 January 2002 to 31 December 2016. Results: A progressive year-on-year decline in corneal donors was found over the study period, from 565 donors per year in 2002 to 89 donors in 2016. As a direct result, there has been an 85.5% decrease in the number of corneal transplants performed per year using locally donated corneas, from 1049 in 2002 to 152 in 2016. 48.8% of donors originated from mortuaries, 39% from private hospitals and 12.2% from government hospitals. Donors originating from mortuaries showed the most significant declines over the 15 year period, decreasing by 94.8%. 79.3% of donated corneas were allocated to the private sector while 21.7% were allocated to the public sector. Demographic data showed that 69.1% of donors were male, while 30.9% were female. 77.2% were white, 14.0% coloured, 6.3% black and 2.5% Indian/Asian. Age of donors demonstrated a bimodal peak, at 25 and 55 years. Conclusion: The number of corneal donations in South Africa has markedly declined, causing the burden of corneal disease requiring corneal transplantation to continually rise. This study describes the magnitude and trends of the current problem in South Africa. The demographic data has identified certain low donor rate groups within the South African population, where there are possible cultural and other objections to corneal donation. These should serve as a major focus of future research and initiatives aimed at reversing the current trends.